Exploring the Landscape of the Internet of Things: Innovations, Applications, and Challenges - Bochare, Sahas; Patil, Krupa; Patil, Maya (Journal of Knowledge in Data Science and Information Management, 2025)
This collection of research papers provides a multifaceted view of the Internet of Things (IoT), exploring its foundational concepts, technological underpinnings, diverse applications, significant challenges, current research trends, and future directions. The vision of IoT involves connecting physical objects to the internet to enable information exchange, leading to innovative services and increased efficiency. Definitions of IoT vary, reflecting perspectives from network and object integration viewpoints across academic and industry communities. The sources collectively highlight a wide spectrum of IoT application areas, including healthcare, environmental monitoring, smart cities, and commercial, industrial, and infrastructural domains. Specific applications discussed range from ecological monitoring and wastewater treatment to industrial automation (Industry 4.0), pervasive computing scenarios, and military/defence systems. Smart cities emerge as a prominent application area, analysed through the lens of IoT-based systems for tasks like video surveillance and air pollution monitoring, and bibliometric studies tracing global research activity and trends. Key technological drivers and architectural aspects of IoT are examined. This includes the layered architecture (network, perception, interface, and service layers) and the interplay of software and hardware components. Various communication technologies enabling IoT are reviewed, such as Wireless Sensor Networks (WSN), particularly important for Industry 4.0 and smart city applications, and advanced connectivity solutions aimed at supporting massive connections, including Compressive Sensing (CS), non-orthogonal multiple access (NOMA), massive Multiple- Input Multiple-Output (mMIMO), and Machine Learning (ML) based random access. Technologies like LPWANs (LoRaWAN, DASH7, NB-IoT), cellular-IoT, and 5G are also relevant.